Characterization and comparison of gene-centered human interactomes. Issue 6 (19th May 2021) - Mosca, Ettore; Bersanelli, Matteo; Matteuzzi, Tommaso; Di Nanni, Noemi; Castellani, Gastone; Milanesi, Luciano; Remondini, Daniel
Abstract: The complex web of macromolecular interactions occurring within cells—the interactome—is the backbone of an increasing number of studies, but a clear consensus on the exact structure of this network is still lacking. Different genome-scale maps of human interactome have been obtained through several experimental techniques and functional analyses. Moreover, these maps can be enriched through literature-mining approaches, and different combinations of various 'source' databases have been used in the literature. It is therefore unclear to which extent the various interactomes yield similar results when used in the context of interactome-based approaches in network biology. We compared a comprehensive list of human interactomes on the basis of topology, protein complexes, molecular pathways, pathway cross-talk and disease gene prediction. In a general context of relevant heterogeneity, our study provides a series of qualitative and quantitative parameters that describe the state of the art of human interactomes and guidelines for selecting interactomes in future applications.